PROVIDING OF PERSONAL DATA PROTECTION BY PUBLIC AUTHORITIES UNDER CONDITIONS OF THE WAR - Pashinskyi, V.; Tsomenko, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The paper is dedicated to issues on analysis of providing of personal data protection by Public Authorities under conditions of the war. It was noticed, that under conditions of wide-scale military aggression, an appropriate attention has to be paid to issues on military personnel personal data protection, as an unauthorized access to these personal data may be dangerous for the life of military personnel. There is outlined, a significant condition for providing of personal data protection has to be a control of information environment. It must stop uncontrolled posting on social networks of numerous pages with photos and videos of Ukrainian military prisoners with their personal data. These measures have features of antiUkrainian propaganda; also, they violate rights of military prisoners, including rights for personal data protection. Receiving the access to personal data of military prisoners, the enemy can use these data to intimidate relatives or State Authorities of Ukraine, to expand panic, or for others hybrid means of informational elements of the war. To provide military personnel personal data protection, it is necessary to work-out particular information registers of categories of persons, mentioned above and to provide different levels of access to its. However, it is necessary to regulate possibilities of receiving information about subjects that are included into the data base, or vice versa, receive an information about absence of data about specific persons. It allows to prevent to violations of rights of military personnel. The issue on determination of competencies of State Authorities in the field of providing of personal data protection of citizens in conditions of the war requires to be resolved. The establishing of Interdepartmental Coordination Center for Registration, Exchange and Return of Prisoners, Missing and Dead is suggested.
Keywords: personal data, providing of protection, authorities, military personnel, prisoners of war, state registers